UDANG ROSTRIS (Litopenaeus stylirostris) KOMODITAS PROSPEKTIF BAGI USAHA PERTAMBAKAN - Bambang Sumartono; Joko Sumarwan; Endah Winarni (Jurnal Perikanan Universitas Gadjah Mada, 2004)
Blue shrimp (Litopenaeus stylirostris) known as “SS” (Super Shrimp) originated as wild larvae from Panama, and is currently in its 22nd generation of domestication. They have undergone a systematic process of selection for enhancement of growth and fecundity, and in particular, for resistance improvement to the IHHN virus.The SS-blue shrimp are significantly more tolerant to low water temperatures than Penaeus monodon or Litopenaeus vannamei. This characteristic was effluent to the broodstock management of blue shrimp. The critical phase of larval rearing is on the interchange from zoea to mysis, but almost no mortality on the post larvae stadium.  It was observed during larvae rearing using modulation system indicated by the survival rate of nauplius to PL 5 was 29%, but PL 5 to PL 15 reached 97%.  Growth of larvae and post larvae in the modulation and non modulation systems were not significant different, but performance and uniformity of the seed in modulation system shown better.  Its avarage production in grow out pond was 9,000 kg/ha with final survival rate of 74.5-94.8%, and avarage daily growth (ADG) of 0.176 g. The ponds were stocked with SS-shrimp at densities of 33-38/m2.